Wise use of coastal wetlands: 10-year reclamation vs. 3-year eco-governance in the Tiaozini Wetland, Jiangsu, China - Liang, Jiahui; Tian, Jiahui; Zuo, Ping; Dai, Ziyi; Jiang, Wenkui; Jin, Juan; Yan, Yuru (Frontiers in Marine Science, 2023)
Coastal wetlands provide extensive ecological services for life on earth, facing rapid disappearance globally influenced by human activities and climate change. From 1984 to 2018, the natural coastal wetlands in China lost about 28% due to sea water intrusion, reduced sediment acquisition, urbanization and reclamation. Nevertheless, in recent years, more and more wetlands have been shifted to protection and rehabilitation from exploitation. The wise use and sustainable development of wetlands become both a challenge and an opportunity for wetlands restoration. We analyzed 3 years of top-down eco-governance and bottom-up activities of Tiaozini, one of the typical wetlands presenting the current policy. Collaboration of stakeholders (the management company, local residents, tourists, scientific committee, NGOs, and media) was also discussed in this study, including public participation and environmental education. Adaptive management, ecosystem-based management, and natural-based solutions play very important roles in eco-governance from both bottom-up and top-down approaches. Results showed that 3-years of eco-governance have witnessed great achievements in both biodiversity conservation and ecotourism development, which outwits 10-year reclamation for coastal wetlands exploitation.